2016
DOI: 10.1088/0964-1726/25/6/065014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Peano fluidic muscle and the effects of its material properties on its static and dynamic behavior

Abstract: The promise of wearable assistive robotics cannot be realized without the development of actuators that mimic the behavior and form of biological muscles. Planar fluidic muscles known as Peano muscles or pouch motors have the potential to provide the high force and compliance of McKibben pneumatic artificial muscles with the low threshold pressure of pleated pneumatic artificial muscles. Yet they do so in a soft and slim form that can be discreetly distributed over the human body. This work is an investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…It occurs over the full stroke of the muscle at a given pressure. Veale et al [45] [51] generalized kinetic friction viscous terms. They also have physically meaningful coefficients.…”
Section: Damping Force Modelsmentioning
confidence: 99%
“…It occurs over the full stroke of the muscle at a given pressure. Veale et al [45] [51] generalized kinetic friction viscous terms. They also have physically meaningful coefficients.…”
Section: Damping Force Modelsmentioning
confidence: 99%
“…Sarosi et al [27] developed a new dynamic model for an actuator as a pneumatic artificial muscle (PAM) with twodirectional motion and found that the dynamic properties of the system were close to the experimentally determined characteristics. Veale et al [28] proposed a novel planar fluidic artificial muscle and analyzed its static and dynamic behaviors by a parallel ideal contractile unit and viscoelastic element.…”
Section: Introductionmentioning
confidence: 99%
“…Another type of soft actuator is a Peano-fluidic muscle (Niiyama et al, 2014(Niiyama et al, , 2015Park et al, 2014;Veale et al, 2016) which is made of materials such as fabric or PVC film. Its structure consists of a few layers that lie flat in their initial state and are bonded at intervals in lines perpendicularly to the contraction direction.…”
Section: Introductionmentioning
confidence: 99%